Polyclonal Expansion of NKG2C+ NK Cells in TAP-Deficient Patients - Béziat, Vivien; Sleiman, Marwan; Goodridge, Jodie P.; Kaarbø, Mari; Liu, Lisa L.; Rollag, Halvor; Ljunggren, Hans-Gustaf; Zimmer, Jacques; Malmberg, Karl-Johan (Frontiers in Immunology, 2015)
Adaptive natural killer (NK) cell responses to human cytomegalovirus infection are characterized by the expansion of NKG2C+ NK cells expressing self-specific inhibitory killer-cell immunoglobulin-like receptors (KIRs). Here, we set out to study the HLA class I dependency of such NKG2C+ NK cell expansions. We demonstrate the expansion of NKG2C+ NK cells in patients with transporter associated with antigen presentation (TAP) deficiency, who express less than 10% of normal HLA class I levels. In contrast to normal individuals, expanded NKG2C+ NK cell populations in TAP-deficient patients display a polyclonal KIR profile and remain hyporesponsive to HLA class I-negative target cells. Nonetheless, agonistic stimulation of NKG2C on NK cells from TAP-deficient patients yielded significant responses in terms of degranulation and cytokine production. Thus, while interactions with self-HLA class I molecules likely shape the KIR repertoire of expanding NKG2C+ NK cells during adaptive NK cell responses in normal individuals, they are not a prerequisite for NKG2C+ NK cell expansions to occur. The emergence of NKG2C-responsive adaptive NK cells in TAP-deficient patients may contribute to antiviral immunity and potentially explain these patients’ low incidence of severe viral infections.